cPanel Server Hosting Security Against Malware and DDoS Attacks on the Open Journal System Platform - Anshari Nur, Muh Nadzirin; Hijriani (Universitas Negeri Semarang, 2024)
Purpose: This research analyzes the security of cPanel in protecting Open Journal Systems (O.J.S.) from DDoS attacks and malware infections. Since contemporary threats to this environment are continuously evolving, this investigation seeks to offer empirical findings and applicable suggestions for platform managers of academic publishing platforms. Methods: The method applies the scope of the literature study and tests system-specific security using cpanel features to test Imunify360, SSL Manager, IP Blocker, Site Quality Monitoring, Awstats, and Jetbackup. This is then followed by observing the server logs on cPanel, where any suspicious activities or signs of attacks can be identified. It contributes to the detection of attack patterns and weaknesses in a system. Result: This indicates several default settings within cPanel were found to be vulnerable and could allow exploitation for DDoS purposes. Tools available in cPanel helped eliminate malware and strengthen defense against DDoS attacks. This is verified by the AWStats check, which means a quicker and more secure access time from the server. Novelty: This study combines many security features and tools from cPanel to implement a complete manner of detecting and improving its security. This method will not only help find out what the weak points are but also provide actionable solutions that can be employed to secure your application. The research results offer a practical guide for system administrators to enhance cPanel security configurations. This includes applying amended security settings and using more tools to safely sweep O.J.S. from online threats.